2011
DOI: 10.1016/j.jtcvs.2010.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Selective antegrade cerebral perfusion during aortic arch surgery confers survival and neuroprotective advantages

Abstract: Antegrade cerebral perfusion was associated with improved survival and neurologic outcomes in patients undergoing aortic arch surgery, especially for cases requiring prolonged aortic arch repair periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The stroke rate in arch surgery has been reported to be 0% to 15%. [8][9][10][11][12] Our results are well within this range. One randomized control study compared the cerebral protection strategies in aortic arch surgery 7 and showed that DHCA alone was superior in postoperative long-term neurocognitive tests.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The stroke rate in arch surgery has been reported to be 0% to 15%. [8][9][10][11][12] Our results are well within this range. One randomized control study compared the cerebral protection strategies in aortic arch surgery 7 and showed that DHCA alone was superior in postoperative long-term neurocognitive tests.…”
Section: Discussionsupporting
confidence: 78%
“…Multiple retrospective studies have shown contradictory outcomes in mortality and neurologic complications. 8,[10][11][12] Even in a study showing a survival benefit with ACP, this benefit was limited to total aortic arch surgery. 9 The Achilles heel of DHCA alone as a cerebral protection strategy has been that the risks of neurologic dysfunction increase after a short period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This supports currently available data, primarily that ACP and RCP yield superior neuroprotection results to those of isolated DHCA. [7][8][9] Most surgeons agree that for arch repairs with short periods of cerebral ischemia (ie, <25 minutes), the use of either ACP, RCP, or isolated DHCA provides sufficient protection. Similarly, the consensus opinion is that for arch repairs with longer ischemic times, some sort of brain perfusion, whether it be ACP or RCP, is beneficial.…”
mentioning
confidence: 99%